2002
DOI: 10.1007/s102010200001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of suspended solids in Lake Biwa by measuring their elemental composition of Al, Si, P, S, K, Ca, Ti, Mn, and Fe

Abstract: We investigated the concentrations of particulate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Concentrations of particulate car- bon and nitrogen were measured with a CHN analyzer (PE-2400II, Perkin Elmer), whereas particulate phosphorus was determined as SRP after wet oxidization (Pujo-Pay and Raimbault 1994). Although these analyses do not discriminate inorganic and organic forms of particulate matter, we interpret these data as representing the concentrations of POC and particulate organic nitrogen (PON) and phosphorus (POP); we could ignore the possibility that calcium carbonate composes a large fraction of particulate carbon because particulate calcium concentrations are typically low in the area studied (Ͻ1 mol L Ϫ1 ; Mito et al 2002). Dissolved oxygen concentration was determined by the Winkler method.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of particulate car- bon and nitrogen were measured with a CHN analyzer (PE-2400II, Perkin Elmer), whereas particulate phosphorus was determined as SRP after wet oxidization (Pujo-Pay and Raimbault 1994). Although these analyses do not discriminate inorganic and organic forms of particulate matter, we interpret these data as representing the concentrations of POC and particulate organic nitrogen (PON) and phosphorus (POP); we could ignore the possibility that calcium carbonate composes a large fraction of particulate carbon because particulate calcium concentrations are typically low in the area studied (Ͻ1 mol L Ϫ1 ; Mito et al 2002). Dissolved oxygen concentration was determined by the Winkler method.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in the present work, this value was used as the terrigeneous Mn/Al ratio. Mito et al (2002) measured particulate element/Al ratios in the northern and southern basins of Lake Biwa during the circulation period and reported 3.0 ¥ 10 -1 mol/mol for Fe/Al, 8.3 ¥ 10 -2 mol/mol for Ca/Al, and 5.6 ¥ 10 -3 mol/mol for Mn/Al. The element/Al ratios obtained in this study also agree well with those of Mito et al MCAR, mean crustal abundance ratio a Elemen/Al ratio is the slope of the linear regression line in Fig.…”
Section: Estimation Of Terrigeneous and Authigenic Fractions In Partimentioning
confidence: 98%
“…However, we cannot immediately use the MCAR, because the MCAR may be different from the element/Al ratio in limnetic terrigeneous matter that reflects the specific geology of the drainage area. Therefore, Sholkovitz and Copland (1982) and Mito et al (2002) assumed that biological and geochemical activity was very low in winter months when the lake was completely overturned, and estimated the element/Al ratio for limnetic terrigeneous matter from the ratio in the suspended particulate matter from that period. We also obtained the element/Al ratios in the terrigeneous matter of Lake Biwa in the same manner as the above reports.…”
Section: Estimation Of Terrigeneous and Authigenic Fractions In Partimentioning
confidence: 99%
See 1 more Smart Citation
“…These elements are effectively transformed into particulate matter through uptake by phytoplankton, oxidation, and adsorption in the basins. In a previous paper (Mito et al 2002), we demonstrated that suspended particulate matter in the North Basin contains substantial authigenic fractions of Si, P, Mn, and Fe. The particulate matter is scavenged and precipitated on sediments or discharged as suspended particles.…”
Section: Discussionmentioning
confidence: 98%